Interventional Techniques for Bone and Musculoskeletal Soft Tissue Tumors: Current Practices and Future Directions - Part I. Ablation - Dalili, Danoob; Isaac, Amanda; Bazzocchi, Alberto; Åström, Gunnar; Bergh, Jonas; Lalam, Radhesh; Weber, Marc-André; Fritz, Jan; Mansour, Ramy (Seminars in Musculoskeletal Radiology, 2020)
Musculoskeletal (MSK) image-guided oncologic intervention is an established field within radiology. Numerous studies have described its clinical benefits, safety, cost effectiveness, patient satisfaction, and improved quality of life, thereby establishing image-guided oncologic intervention as a preferred pathway in treating patients presenting with specific benign MSK tumors. But there is a paradigm shift on the horizon because these techniques may also support established pillars (surgery, systemic treatment, radiotherapy) in the treatment of malignant MSK tumors. Unlike benign tumors, where they are used as primary therapy lines with curative intent, such interventions can be selected for malignant tumors as adjuvant treatment in painful or unstable bone or soft tissue lesions or as more palliative therapy strategies. Using examples from our clinical practices, we elaborate on the benefits of applying a multidisciplinary approach (traditionally involving MSK radiologists, oncologists, orthopaedic surgeons, microbiologists, pathologists, physiotherapists, and pain management experts), ideally within a sarcoma treatment center to deliver a patient-specific therapy plan and illustrate methods to assess the benefits of this model of care.In this article, we review the current repertoire of ablation techniques, demonstrate why such procedures offer value-based alternatives to conventional treatments of specific tumors, and reflect on future directions. Additionally, we review the advantages and limitations of each technique and offer guidance to improve outcomes.
Keywords: musculoskeletal intervention; tumor; ablation; sarcoma; metastasis